Numerical solution of source identification multi-point problem of parabolic partial differential equation with Neumann type boundary condition - Ashyralyyev, C.; Ashyralyyeva, T.A. (Bulletin of the Karaganda University. Mathematics Series, 2024)
We study a source identification boundary value problem for a parabolic partial differential equation with multi-point Neumann type boundary condition. Stability estimates for the solution of the overdetermined mixed BVP for multi-dimensional parabolic equation were established. The first and second order of accuracy difference schemes for the approximate solution of this problem were proposed. Stability estimates for both difference schemes were obtained. The result of numerical illustration in test example was given.